2016
DOI: 10.1186/s12884-016-0973-1
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal physical activity: a qualitative study exploring women’s experiences and the acceptability of antenatal walking groups

Abstract: BackgroundRegular physical activity (PA) can be beneficial to pregnant women, however, many women do not adhere to current PA guidelines during the antenatal period. Patient and public involvement is essential when designing antenatal PA interventions in order to uncover the reasons for non-adherence and non-engagement with the behaviour, as well as determining what type of intervention would be acceptable. The aim of this research was to explore women’s experiences of PA during a recent pregnancy, understand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 38 publications
4
18
0
Order By: Relevance
“…Likewise, the UK Chief Medical Officers produced guidelines for PA in pregnancy [30]. Despite this, most participants perceived a lack of guidance from healthcare professionals, which is consistent with findings from other studies [21,22,27,[31][32][33][34]. In addition, when participants did receive advice from healthcare professionals, or sports trainers, they often felt like this advice was contradictory and overly cautious.…”
Section: Discussionsupporting
confidence: 71%
“…Likewise, the UK Chief Medical Officers produced guidelines for PA in pregnancy [30]. Despite this, most participants perceived a lack of guidance from healthcare professionals, which is consistent with findings from other studies [21,22,27,[31][32][33][34]. In addition, when participants did receive advice from healthcare professionals, or sports trainers, they often felt like this advice was contradictory and overly cautious.…”
Section: Discussionsupporting
confidence: 71%
“…Preliminary framework of factors influencing mode choice when travelling with young children. (Pooley et al, 2014); 12 (Rubin et al, 2014); 13 (Dowling, 2015); 14 (Thomas, 2016); 15 (Dowling, 2000); 16 (Sattlegger & Rau, 2016); 17 (Price & Matthews, 2013); 18 (Lanzendorf, 2010); 19 (Currie, Gray, Shepherd, & McInnes, 2016); 20 (Bean, Kearns, & Collins, 2008); 21 (McDonald, 2006); 22 (Wheatley, 2014); 23 (McQuaid & Chen, 2012); 24 (Scheiner, 2014); 25 (Rothman et al, 2016); 26 (Birken et al, 2015); 27 (Taubman-Ben-Ari & Noy, 2011); 28 (Zwerts, Janssens, & Wets, 2008). Symbols: −, negative impact on mode; +, positive impact on mode; −/+, neutral impact on mode; ?, unknown.…”
Section: What Factors Influence Mode Choice Among Families With Youngmentioning
confidence: 99%
“…The interconception period represents a window of opportunity to help women improve their health, thus reducing the risk of adverse outcomes related to excess weight or stress in subsequent pregnancies (Athukorala et al, 2010; DiPietro, 2004; O’Donnell et al, 2009; Thomas et al, 2014). The interconception period begins immediately following childbirth and ends with a subsequent conception (Currie et al, 2016; Huberty et al, 2013). The post-partum period, typically considered the first 6–12 months following childbirth (Antheunis et al, 2013; Lagan et al, 2010) is included in the interconception period.…”
Section: Rationalementioning
confidence: 99%
“…Other studies have found that the ability to cope well with stress may play a larger role in weight management efforts than simply the presence or lack of stress itself (Gormally & Rardin, 1981; Grilo et al, 1989; Westenhoefer et al, 2004), which would then seem to warrant inclusion of stress management education and strategies in a weight loss program; however, this has not been investigated in an interconception population. Similarly, while mind–body approaches seem especially well suited to address the interrelated nature of weight and stress management, studies of these techniques have not been implemented in interconception populations, despite evidence suggesting they would likely be effective and well received by the target audience (Currie et al, 2016). …”
Section: Critical Evaluation Of Current State Of Knowledgementioning
confidence: 99%